2014
DOI: 10.5751/ace-00650-090106
|View full text |Cite
|
Sign up to set email alerts
|

Chronic lack of breeding by Galápagos Blue-footed Boobies and associated population decline

Abstract: ABSTRACT. A survey of Blue-footed Boobies (Sula nebouxii excisa) throughout the taxon's range in Galápagos, Ecuador found ~6400 adults, compared to a rough estimate of 20,000 in the 1960s. Few pairs bred in 2011-2013 and almost no birds in juvenile plumage were seen. Long-term data suggest that poor breeding began in 1998. Lack of recruitment over this period would mean that the current population is mostly elderly and experiencing senescent decline in performance. Anthropogenic effects such as introduced pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 47 publications
2
13
0
1
Order By: Relevance
“…Although nesting effort was better in colonies on the range peripheries, it was still sub-optimal. This breeding failure in pelicans was similar to that observed in many other Pacific seabirds (e.g., Anchundia et al 2014, Humphries et al 2015, MacCall et al 2016), but apparently not universal in all Pacific seabirds .…”
Section: Synthesis and Conclusionsupporting
confidence: 86%
“…Although nesting effort was better in colonies on the range peripheries, it was still sub-optimal. This breeding failure in pelicans was similar to that observed in many other Pacific seabirds (e.g., Anchundia et al 2014, Humphries et al 2015, MacCall et al 2016), but apparently not universal in all Pacific seabirds .…”
Section: Synthesis and Conclusionsupporting
confidence: 86%
“…Taking low-frequency oscillations into account is at an early stage but is absolutely necessary in the context of global warming. Failing to consider low-frequency oscillations among the possible causes of fluctuations in tropical seabirds (Anchundia et al 2014) could lead to strong bias in reporting responses to regional climate warming.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, they cause large changes to marine ecosystems (Alheit et al 2009), such as alternative regimes of sardines and anchovy abundance observed across the major upwelling areas of the world (Lluch-Cota 2013). Demographic and behavioral responses of high trophic-level predators to these regime shifts have been suggested (Lusseau et al 2004, Baker et al 2012, Hatch 2013, Anchundia et al 2014, Tompkins et al 2017) but, to our knowledge, never documented in detail, in particular for survival rates. Seabirds, mammals, and reptiles have complex life cycles with delayed maturity and intermittent reproduction that are not easily amenable to demographic analysis (deYoung 2004).…”
Section: Introductionmentioning
confidence: 92%
“…This result adds to the current evidence of an overall declining trend in seabird populations around the world (Croxall et al 2012, Paleczny et al 2015 and extends its confirmation to the warm eastern tropical Pacific. Declining numbers of these boobies have also been documented in the Galápagos Archipelago by comparing estimates of population size from the 2000s with estimates from the 1960s (Anchundia et al 2014), suggesting this negative trend could be taking place throughout the entire distribution range of this species. Interestingly, although l decreased over time, the long-term average suggests population increase (mean l  1.11  0.052).…”
Section: Discussionmentioning
confidence: 84%
“…In this study, we used 23 yr of data to investigate how adult survival, local recruitment, and their relative contributions to population growth (l) vary over time in the blue-footed booby, a long-lived locally foraging seabird that breeds on islands in the warm eastern tropical Pacific (Nelson 2005). Chronic lack of breeding by blue-footed boobies and low counts of breeding pairs and juveniles have been observed in recent years in the Galápagos Archipelago, suggesting that population numbers of these tropical boobies could be declining (Anchundia et al 2014). Our study population in Mexico contains a large number and proportion (∼ 90% in 2006) of marked individuals for which survival and recruitment probabilities can be estimated.…”
mentioning
confidence: 91%